Gene expression profiles of the meniscus avascular phenotype: A guide for meniscus tissue engineering. Issue 7 (14th March 2018) - Grogan, Shawn P.; Duffy, Stuart F.; Pauli, Chantal; Lotz, Martin K.; D'Lima, Darryl D.
ABSTRACT: Avascular (Avas) meniscus regeneration remains a challenge, which is partly a consequence of our limited knowledge of the cells that maintain this tissue region. In this study, we utilized microarrays to characterize gene expression profiles of intact human Avas meniscus tissue and of cells following culture expansion. Using these data, we examined various 3D culture conditions to redifferentiate Avas cells toward the tissue phenotype. RNA was isolated from either the tissue directly or following cell isolation and 2 weeks in monolayer culture. RNA was hybridized on human genome arrays. Differentially expressed (DE) genes were identified by ranking analysis. DAVID pathway analysis was performed and visualized using STRING analysis. Quantitative PCR (qPCR) on additional donor menisci (tissues and cells) were used to validate array data. Avas cells cultured in 3D were subjected to qPCR to compare with the array‐generated data. A total of 387 genes were DE based on differentiation state (>3‐fold change; p < 0.01). In Avas‐cultured cells, the upregulated pathways included focal adhesion, ECM‐receptor interaction, regulation of actin cytoskeleton, and PDGF Signaling. In 3D‐cultured Avas cells, TGFβ1 or combinations of TGFβ1 and BMP6 were most effective to promote an Avas tissue phenotype. THBS2 and THBS4 expression levels were identified as a means to denote meniscus cell phenotype status. We identified the key gene expression profiles, new markers and pathways involved in characterizing the Avas meniscus phenotype in the native state and during in vitro dedifferentiation and redifferentiation. These data served to screen 3D conditions to generate meniscus‐like neotissues. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1947–1958, 2018.